3D multi-channel bi-functionalized silk electrospun conduits for peripheral nerve regeneration. (January 2015) - Dinis, T.M.; Elia, R.; Vidal, G.; Dermigny, Q.; Denoeud, C.; Kaplan, D.L.; Egles, C.; Marin, F.
Abstract: Despite technological advances over the past 25 years, a complete recovery from peripheral nerve injuries remains unsatisfactory today. The autograft is still considered the "gold standard" in clinical practice; however, postoperative complications and limited availability of nerve tissue have motivated the development of alternative approaches. Among them, the development of biomimetic nerve graft substitutes is one of the most promising strategies. In this study, multichanneled silk electrospun conduits bi-functionalized with Nerve Growth Factor (NGF) and Ciliary Neurotropic Factor (CNTF) were fabricated to enhance peripheral nerve regeneration. These bioactive guides consisting of longitudinally oriented channels and aligned nanofibers were designed in order to mimic the fascicular architecture and fibrous extracellular matrix found in native nerve. The simple use of the electrospinning technique followed by a manual manipulation to manufacture these conduits provides tailoring of channel number and diameter size to create perineurium-like structures. Functionalization of the silk fibroin nanofiber did not affect its secondary structure and chemical property. ELISA assays showed the absence of growth factors passive release from the functionalized fibers avoiding the topical accumulation of proteins. In addition, our biomimetic multichanneled functionalized nerve guides displayed a mechanical behavior comparable to that of rat sciatic nerve with an ultimate peak stress of 4.0±0.6 MPa and a corresponding elongation at failure of 156.8±46.7%. Taken together, our results demonstrate for the first time our ability to design and characterize a bi-functionalized nerve conduit consisting of electrospun nanofibers with multichannel oriented and nanofibers aligned for peripheral regeneration. Our bioactive silk tubes thus represent a new and promising technique towards the creation of a biocompatible nerve guidance conduit.